Cutaneous Adverse Drug Reaction in Morocco – Evaluating the Knowledge of Pharmacists - Youssef Moutaouakkil1 , Esso Eric Valery Latt1 , Rachid el Jaoudi2 , Mina Ait el cadi2 , Yahia Cherr (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background. Pharmacy professionals, as the most available members of medical team, have an important role in educating patients about Cutaneous Adverse Drug Reaction (CADR). Our aim was to evaluate pharmacists’ knowledge of the cutaneous drug reaction, and their recommendations under hypothetical situations, through a written questionnaire. Methods. based cross-sectional study was conducted among community pharmacists working at the private sector of the rabat-salé-zemmour-zaer region using a structured interviewing questionnaire. Results. Ninety- eight pharmacists completed the questionnaire (response rate 48%). The mean overall score was 52.87 ± 23.19% correct answers. The majority of pharmacists (66,32 %) estimated that they view more than a Patient with CADR each month, and only forty-seven pharmacists underwent CADR related training during the year preceding the survey. Pharmacists obtained the highest correct scores on the true/false statements inquiring about Cutaneous reaction due to drugs definition, classification and the most common medication classes implicated in Cutaneous reaction due to drugs, Overall, the true/false questions were relatively easier to address, compared with the multiple choice questions (63.60 ± 13.15% vs. 51.18 ± 24.12%, respectively; p < 0.01). Only 14 pharmacists were familiar with Cutaneous reaction due to drugs sach as ( Drug Reaction With Eosinophilia, contact dermatitis, Nail Disorders, bullous pemphigoid ). Longer time since training completion was associated with a lower total score (38,77 ± 9% vs. 61,22 ± 11% for the pharmacists who were in practice 5 years or less and those with longer time in practice, respectively; p < 0.05). Conclusion. Pharmacists were knowledgeable regarding some aspects of CADR. However, our study, as in previous studies among health care professionals, identified some gaps in knowledge. These findings indicate the need for better education of pharmacists regarding CADR and its supported.